Answer: Are you going to attach any work?
Step-by-step explanation:
Point-slope form is y - y1 = m (x + x1)
First you need to find m [slope] by subtract y2 and y1 and divide it by the outcome of x2 - x1
13 - (-9) = 22
-2 - 9 = -11
22/-11 = -2
Plug in the first point (as instructed) into the equation.
y - (-9) = -2 (x - 9)
Simplify the beginning.
y + [9] = [-2] (x + [-9])
(The brackets are the fill in the blanks)
I think it is a glide reflection.
Answer:
for the first one its: y=-3/4x+9
for the second one its: already done
Step-by-step explanation: